2016
DOI: 10.1080/13557858.2016.1244738
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse, depressive symptoms, and HIV/STI risks of US Hispanic women

Abstract: Objectives Alcohol misuse and depressive symptoms have been linked to HIV/STI risk, but studies have rarely included Hispanic women, who have over four times greater HIV incidence than white, non-Hispanic women. Understanding the connections among alcohol misuse, depressive symptoms, and HIV/STI risks may suggest ways to meet specific needs of Hispanic women. This study’s objective is to examine the relationships among alcohol misuse, depressive symptoms, and seven HIV/STI risk factors. Design Five hundred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…commonly cited in the literature as having associations with increased risk of HIV infection, particularly among Hispanic women. 10,13,40,41 Depressive symptoms had also significantly reduced by the 12-month follow up of SEPA. The importance of this outcome in validating the effectiveness of the SEPA program should be examined within the context that females and persons of Hispanic origins respectively have the highest and second highest rates of depression in the United States.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…commonly cited in the literature as having associations with increased risk of HIV infection, particularly among Hispanic women. 10,13,40,41 Depressive symptoms had also significantly reduced by the 12-month follow up of SEPA. The importance of this outcome in validating the effectiveness of the SEPA program should be examined within the context that females and persons of Hispanic origins respectively have the highest and second highest rates of depression in the United States.…”
Section: Discussionmentioning
confidence: 89%
“…42 More importantly, significant associations between depressive symptoms and HIV risk among Hispanic women exist in the literature. 40 Depressive symptoms have also been found to inversely correlate with self-esteem among Hispanic women. 43 The decreased incidence of depressive symptoms in our study may have resulted from the cultural tailoring of the SEPA program, which allowed women to openly discuss their concerns and fears about HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that 58% of the population consumes alcohol and 25% consume drugs. Some studies mention a connection with alcohol abuse, depressive symptoms and the risk of contracting a sexually transmitted infection [28]. This evidence leads us to study the frequencies of STIs in our population, as well as their relationship with other studies.…”
Section: Discussionmentioning
confidence: 56%